Soil Organic Matter Research and Climate Change: Merely Re-storing Carbon Versus Restoring Soil Functions - Baveye, Philippe C.; Schnee, Laura Sophie; Boivin, Pascal; Laba, Magdeline; Radulovich, Ricardo (Frontiers in Environmental Science, 2020)
Over the last two decades, the sequestration of carbon in soils has often been presented as a possible way to mitigate the steady increase in the concentration of CO2 in the atmosphere, one of the most commonly mentioned causes of climate change. A large body of literature, as well as sustained efforts to attract funding for the research on soil organic matter, have focused on the soil carbon sequestration – climate change nexus. However, because CO2 is not the only greenhouse gas released by soils, and given the fact that the feasibility of large-scale carbon sequestration remains controversial, this approach does not appear optimal to convince policy makers. In this perspective article, we argue that a far better strategy revolves around the effect of climate change on functions/services that soils render. In particular, since climatologists forecast less frequent but more intense rainfall events in the future, which may lead to food shortages, catastrophic flooding, and soil erosion if soils are not able to cope, a more suitable focus of the research would be to increase soil organic matter content so as to strengthen the water regulation function of soils. The different conceptual and methodological shifts that this new focus will require are discussed in detail.